Radiographic appearance of extracorporeal membrane oxygenations versus left ventricular assist device. (May 2021) - Mackie, Phillip M; Peek, Giles J; Jacobs, Jeffrey P; Bleiweis, Mark S
Abstract: Chest radiography compares left ventricular decompression in the same patient supported with extracorporeal membrane oxygenation with atrial septal fenestration and subsequently supported with left ventricular assist device with apical cannulation.